ANALISIS KINERJA JARINGAN WIRELESS BERDASARKAN PARAMETER QOS (THROUGHPUT, DELAY, PACKET LOSS) TERHADAP VARIASI TRAFIK JAM OPERASIONAL PADA PENGGUNA DI LINGKUNGAN SEKOLAH DI SMP NEGERI 1 NGARINGAN - Andhika Setyo Utomo, Anang; Supandi, Supandi; Ricky Rozzaqi, Ade (Penerbit Lafadz Jaya, 2025)
Quality of Service (QoS) is the main indicator in assessing the performance of data communication systems. This study aims to analyze network QoS parameters, namely Throughput, Packet Loss, Delay, and Jitter, under two different conditions: when traffic is free and traffic is heavy. Measurements were carried out using a network monitoring device with the TIFON standard reference. The test results showed that the throughput value during leisure traffic was 19 Mbps, while when heavy traffic reached 1,106 Mbps, both were in the Excellent category. Packet loss was recorded at 2.5% at leisure and 1.7% at solid, both in the good category (<3%). The delay in leisure conditions reached 299.1 ms, while when it was busy it was only 7.3 ms. Similarly, jitter experienced a significant decrease from 299.2 ms at leisure to 7.3 ms when it was solid. These findings show that network performance is actually more optimal when traffic is high. Anomalies in leisure conditions, especially high delay and jitter, are thought to be caused by the mechanism of idle system or internal latency. Therefore, it is recommended to optimize the system when the network is in an inactive condition so that the quality of service is maintained consistently.